Frecuency and type of foods received by children under 36 months supplemented with iron in Lambayeque, 2021 - Aliaga Calderón, Ray Marvin (2022)
Objective: To determine the frequency and type of food consumed by children under 36 months of age supplemented with iron at the Toribia Castro Chirinos Health Center - 2021. Method: Quantitative, descriptive, cross-sectional research. We interviewed 136 mothers aged 18 years and older, with children under 36 months, with ferrous supplementation and hemoglobin level higher than 11 g/dl; sampling was by convenience. The questionnaire "frequency of food consumption" (Crombach's alpha 0.75) was applied.  Data were collected through an online questionnaire using Google forms. Descriptive analysis was performed according to nominal variables in the Excel 2021 program. Main results: The mothers expressed that 80% of the children had liver, chicken and eggs prepared for them; 44.12% consumed fish. The fruits always supplied were granadillas and bananas, 87.50% of children consumed fruits in juice. Vegetables used: carrots, bulbs and pumpkin. More than 90% use tubers such as sweet potato and potato, 80% use oatmeal and noodles, 60% quinoa and 98% vegetable oil. It is remarkable the frequent consumption of cookies and chamomile water; more than 90% reported not providing coffee, soft drinks and cocoa; more than 16% were provided with tea and chocolates. Overall conclusion: Food consumption is varied, there is intake of foods rich in heminic and non-heminic iron, low use of iron enhancers and inhibitors.